The Determinants of Bank Profitability in China From 2011 To 2018 - Lu, Tianmin (2019)
In 2001, China's accession to the WTO, along with the opening up of the banking industry, foreign banks have been set up, Chinese banking sector has faced great challenges in the international market, and the internal and external operating environment has undergone drastic changes. In addition, with the implementation of interest rate liberalization and Internet finance, Chinese banking industry are facing not only the impact from foreign banks, but also the brutal competition of domestic financial markets. Therefore, the preferred solution for banks is to improve their profitability, thus enhance their own competitiveness. Therefore, this paper tries to make a tentative study for the determinants of commercial bank profitability. This study collects the relevant data of 47 Chinese commercial banks from 2011 to 2018, adopts the system GMM methods, and chooses ROAE as the dependent variable to study the determinants of Chinese commercial banks' profitability. The empirical results shows that bank asset size, liquidity, credit risk and capital adequacy are negatively correlated with bank profitability, while banks' management efficiency, ZSCORE, GDP growth rate and unemployment rate are positively correlated with bank profitability. Among them, GDP growth rate, bank size, management efficiency, capital adequacy and ZSCORE are the determinants of Chinese commercial banks' profitability.